Hypofractionated reirradiation by conformal radiotherapy techniques in recurrent anaplastic astrocytoma and glioblastoma multiforme: An observational study at a Tertiary Care Center in North India - Shahid Rashid Sofi; Tauseef Ahmad Tali; Waseem Aijaz Kitab; Mushtaq Ahmad Sofi; Mohammad Maqbool Lone; Arshad Manzoor Najmi; Nazir Ahmad Dar (Journal of Radiation and Cancer Research, 2023)
Aim and Objectives: The aims and objectives of the study were to assess the progression-free survival (PFS) and overall survival, local tumor control rate (response rate), effect on the quality of life, and treatment-related toxicities in all patients diagnosed with recurrent high-grade gliomas (HGGs). Methodology: The present study was conducted between September 2017 and July 2019 in the Department of Radiation Oncology, Sheri Kashmir Institute of Medical Sciences and included a total of 22 patients. The study included recurrent HGGs (Grade III/IV) Operated Cases of Grade III and Grade IV. Results: The majority of our patients were between the age group of 40–60 years (45.5%). There were 12 males (54.5%) and 10 females (45.5%). GBM was the most common diagnosis in 13 (59.1) patients and 9 (40.9%) were anaplastic astrocytoma. Sixteen patients were diagnosed as recurrent HGG radiologically. Sixteen (72.7%) patients achieved partial response and 6 (27.3%) achieved stable disease. The median PFS was 2.8 months and the median overall survival was 4.2 months. Conclusion: Reirradiation is one of the treatment options for recurrent HGGs and conformal intensity-modulated radiotherapy can be effective treatment modality for recurrent high-grade brain tumors with only mild side effects. Although survival is better in patients with good performance status and young age.